Predictive Factors for Super Responder Status and Long-Term Effectiveness of Guselkumab in Psoriasis: A Multicenter Retrospective Study - Edoardo Mortato; Marina Talamonti; Lorenzo Marcelli; Matteo Megna; Annunziata Raimondo; Giacomo Caldarola; Nicoletta Bernardini; Anna Balato; Anna Campanati; Maria Esposito; Claudio Bonifati; Viviana Lora; et al. (Dermatology and Therapy)
Abstract Introduction Psoriasis is a chronic inflammatory skin disorder, affecting around 2–3% of the global population. The IL-23/Th17 signaling pathway plays a critical role in disease progression. Guselkumab, an IL-23p19 monoclonal antibody, has shown substantial efficacy in clinical trials for treating moderate-to-severe plaque psoriasis. However, preliminary identification of super responders (SRe: patients achieving PASI 100 at week 20) can help optimize treatment strategies. This study aims to identify predictive factors for SRe status in patients receiving guselkumab therapy for psoriasis and to evaluate long-term effectiveness in the entire cohort and both SRe and non-super-responder (nSRe) groups to understand whether SRe status is also a predictor of long-term response to guselkumab in a real-world setting. Methods A retrospective longitudinal study was conducted at ten Italian centers between January and October 2024. Data from 1008 patients treated with guselkumab for at least 20 weeks were analyzed. Patients were classified as SRe (PASI 100 at week 20) and nSRe. Baseline clinical and anthropometric profiles, comorbidities, and treatment history were collected. Efficacy was evaluated using PASI scores. Logistic regression analysis was performed to identify predictive factors for achieving SRe status. Results Of 1008 patients, 581 (57.6%) were classified as SRe, while 427 (42.4%) were nSRe. SRe patients were more likely to be bio-naïve and had lower baseline PASI scores and comorbidities such as obesity, hypertension, and diabetes. Multivariate logistic regression identified obesity, prior biologic therapy, and a higher baseline PASI as negative predictors for SRe status. Guselkumab demonstrated significant long-term efficacy, with SRe patients achieving sustained PASI 100 in 85% at year 4 and 83.4% at year 5 compared to 54% and 59.2% in nSRe patients, respectively. Conclusions Our study highlights the importance of identifying patients most likely to achieve PASI 100 early in treatment. Factors such as obesity, prior biologic experience, and baseline PASI contribute to predicting complete skin clearance, which can guide clinical decision-making and enable personalized treatment strategies.